Optical code division multiple access : a practical perspective - Kitayama, Ken-Ichi (Cambridge : Cambridge University Press, 2014)
A comprehensive guide to optical fiber communications, from the basic principles to the latest developments in OCDMA for Next-Generation Fiber-to-the-Home (FTTH) systems. Part I starts off with the fundamentals of light propagation in optical fibers, including multiple access protocols, and their enabling techniques. Part II is dedicated to the practical perspectives of Next-Generation Fiber-to-the-Home (FTTH) technology. It covers the key building blocks of OCDMA, devices such as optical encoders and decoders, signal impairments due to noise, and data confidentiality, a unique property of OCDMA. This is followed by hybrid system architectures with TDM and WDM and practical aspects such as system cost, energy efficiency and long-reach PONs. Featuring the latest research, with cutting-edge coverage of system design, optical implementations, and experimental demonstrations in test beds, this text is ideal for students, researchers and practitioners in the industry seeking to obtain an up-to-date understanding of optical communication networks.
Machine generated contents note: 1. Introduction; Part I: 2. Optical multiple access systems; 3. Light propagation in optical fiber; 4. Fundamental of transmission systems; 5. Enabling techniques; Part II: 6. OCDMA principles; 7. Optical encoding and decoding; 8. Data confidentiality; 9. Testbeds of OCDMA systems and its hybrid systems; 10. Practical aspects.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Optical fiber communication; Code division multiple access